The Effect of Financial Literacy and Paylater Payment System on Student Consumptive Behavior in Ciamis Regency in Sharia Economic Perspective - Engkar Rahma Maulida; Eris Munandar; Nila Nurochani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Financial literacy is a knowledge that everyone should know and understand, not just to manage income but to manage their finances well. More and more e-commerce that provide various kinds of payment systems, for example paylater, this is also a reason that someone must understand financial literacy. Students are synonymous with life that follows trends and likes to shop online which in turn causes consumptive behavior because they do not know how to manage finances properly. Therefore, financial literacy is essential for students when facing individual or group financial problems, but its implementation in everyday life will be even better. From this background, this research was conducted with the title "The Influence of Financial Literacy and the Paylater Payment System on Consumptive Behavior of Students in Ciamis Regency in the Perspective of Sharia Economics". This study used quantitative research methods and for primary data collection, data collection techniques were carried out by distributing Google form questionnaires and this study also used purposive sampling as a sampling method so that 100 samples were found, namely students in Ciamis Regency with data analysis using multiple linear regression. The purpose of this research is to find out the effect of financial literacy and the paylater payment system on the consumptive behavior of students in Ciamis Regency in the perspective of Islamic Economics. The results of this study show that the results of the T-test variable financial literacy partially have a negative and significant effect on consumptive behavior (Y) of students in Ciamis Regency, the results of tcount -2.236 and ttable 1.984 means that tcount ttable with a significance of 0.028 0.05. The results of the T-test of the paylater payment system partially have a positive and significant effect on student consumptive behavior, the results of tcount 3.116 and ttable 1.984 mean that tcount ttable with a significance of 0.02 0.05. While the F test obtained Fcount of 8,135 and Ftable of 3.09 meaning that Fcount Ftable with a significance of 0.00 0.05 so the variables of financial literacy and the paylater payment system simultaneously have a positive and significant effect on the consumptive behavior of students in Ciamis Regency